TANGGAPAN KONSUMEN PADA SALESMAN PT. DIVA IKHLAS TOUR & TRAVEL DI PEKANBARU - Claudia, Monica Natasha; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The increase in sales of tour packages for travel agents is inseparable from the important role of the salesman. Salesmen present tour packages offered by the company and influence prospective customers to buy them. This requires the salesman to have salesmanship. The salesmanship of a salesman includes product knowledge, price policy and human relations, which are taken from the combined theories of Richard Sihite (2000: 142) and Ni Luh Henny Andayani (2014: 3). The current study aims to determine consumers? responses to a salesman from PT. Diva Ikhlas Tour & Travel in Pekanbaru. The researcher focused on the 142 consumers who had used the travel services of PT. Diva Ikhlas Tour & Travel in Pekanbaru in 2018. A sample was taken from this number, constituting 35% of the population, or 50 consumers. The sampling technique used in this study was the accidental sampling technique. Data was collected using online questionnaires, observation, interviews and documentation. The measurement technique for the research data employed a Likert scale with five criteria, and descriptive quantitative methods were used for the data analysis. Based on the information obtained from the consumers? responses to this salesman of PT. Diva Ikhlas Tour & Travel in Pekanbaru, his salesmanship is very good. This is evidenced by the results of table recapitulation, with a total score of 1,936 in the score range of 1,890 - 2,250, which concludes that the salesman is skilled at product knowledge, price policy and human relations. If the salesman maintains his salesmanship and presents the tour packages to more prospective customers, the sales of PT. Diva Ikhlas Tour & Travel in Pekanbaru should increase in the years to come. Keywords: salesman, product knowledge, price policy, human relations